Content Validity and Scoring of Two Tier as Measuring Instrument of Science Process Skills for Knowledge Aspects in Chemistry Learning - Yamtinah, Sri; Saputro, Sulistyo; *, Haryono; Utami, Budi (Proceeding of International Conference on Teacher Training and Education, 2016)
Problems in chemistry learning related to the three levels, namely the macroscopic, sub-microscopic, andsymbolic (representational) (Barke, 2009: 27). During chemistry learning, studentâs abilities to understandthe roles of each representation level and transfer to another level is an important aspect for produce anexplanation that can be understood. The curriculum of 2013 mandates that the essence of a scientificapproach to learns through the Science Process Skills. Two-tier used as an instrument for measuringknowledge aspect because its abilities to analyze the cognitive skills of the students. Through two-tier,students just not pick the answer on items but also provide a reason for the answers are chosen so thecognitive processes can be observed and measured. As an instrument to measure the Science Process Skills,Â the fulfillment validity of the content becomes important. This two-tier instrument has good content validityÂ between 0.78 to 1.0. Therefore, the scoring system that used in the examination studentsâ answer sheets isÂ important part of this instrument to analyze science process skills student.